2021
DOI: 10.3389/fvets.2021.675712
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Diets With Bovine Colostrum Influences Immune and Gut Function in Kittens

Abstract: In its early life a kitten faces many significant events including separation from its mother, re-homing and vaccination. The kitten is also slowly adapting to their post-weaning diet. Recent advances in companion animal nutrition have indicated that functional ingredients such as colostrum can help support the immune system and gastrointestinal health. Here we report for the first time the effect of feeding a diet containing 0.1% spray dried bovine colostrum (BC) to growing kittens on gut-associated lymphoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In poultry production, supplementation with bovine colostrum has shown improvements in protein quality, feed conversion efficiency, and growth performance, reducing feed costs and mortality rates [4,26]. In general, when it is consumed as a food supplement, bovine colostrum enhances the immune functions (Figure 1); gut microbiota; and the performance of animals like dogs, cats, horse, and fish [5,[27][28][29].…”
Section: Importance Of Bioactive Components and Animal Health Benefitsmentioning
confidence: 99%
“…In poultry production, supplementation with bovine colostrum has shown improvements in protein quality, feed conversion efficiency, and growth performance, reducing feed costs and mortality rates [4,26]. In general, when it is consumed as a food supplement, bovine colostrum enhances the immune functions (Figure 1); gut microbiota; and the performance of animals like dogs, cats, horse, and fish [5,[27][28][29].…”
Section: Importance Of Bioactive Components and Animal Health Benefitsmentioning
confidence: 99%
“…On the prebiotic side, studies have shown that dietary supplementation of several different prebiotics exert beneficial effects in IBD through changes in the intestinal microflora composition, i.e., increasing beneficial bacteria such as Bifidobacteria and Lactobacilli and improving the intestinal epithelial barrier [70]. Bovine colostrum, for example, has repeatedly been shown to (i) inhibit gut pathogens while stimulating the growth of a healthy microbiota (the so-called eubiotic effect) [71][72][73], (ii) reduce iatrogenic injury to the gut [74], (iii) prevent and limit diarrhoea of different origins [74,75].…”
Section: Dysbiosis and Possible Dietary Interventionsmentioning
confidence: 99%
“…Cow colostrum has several components that are known to strengthen and enhance the immune system. In addition, it contains growth factors and bioactive compounds such as lactoferrin [ 120 , 121 ].…”
Section: Nutraceutical Compounds In Newbornsmentioning
confidence: 99%